Media Sosial sebagai Katalis Pendidikan: Dinamika Gerakan Kesetaraan Gender di Indonesia melalui Perspektif Strukturasi - Ni Wayan Giri Adnyani; Udi Rusadi (Universitas Indraprasta PGRI Jakarta, 2023)
In the context of communication discipline, social media has emerged as a powerful platform for disseminating messages and mobilizing masses for social causes. It can be argued that social media serves as a medium for promoting and advocating social change. This research aims to analyze the role of social media in facilitating the gender equality movement in Indonesia from the perspective of political economy of communication This research focuses on Vincent Mosco's structuration concept by exploring the agency's role in creating social movements regarding gender equality on Instagram. This study uses a qualitative research method with ethnography on social media content related to the gender equality movement in Indonesia. The data collected includes posts, comments and hashtags related to gender issues uploaded on the Instagram platform. This research indicates that Instagram has the potential to play a role in mobilizing and expanding the gender equality movement in Indonesia by enabling youth, advocacy groups, and other individuals to voice gender issues, mobilize support, and spread messages of the movement.